Cerebral Ischemia/Reperfusion Increases Endothelial Nitric Oxide Synthase Levels by An Indomethacin-Sensitive Mechanism - Beasley, Tracy C.; Bari, Ferenc; Busija, David W.; Louis, Thomas; Thrikawala, Nishadi; Thore, Clara (My University, 1998)
In anesthetized piglets, endothelial and neuronal nitric oxide synthase (eNOS and nNOS, respectively) levels were investigated after global cerebral ischemia. Increased intracranial pressure was used to produce 5 or 10 minutes of global ischemia, which was verified visually by observing pial arteriolar blood flow and by a microsphere technique. At 4 to 6 hours of reperfusion, parietal cortex, hippocampus, and cerebellum were collected for immunohistochemical or immunoblot analysis. Immunohistochemical examination localized eNOS only to blood vessels and nNOS only to nonvascular cells, which were primarily neurons in all regions examined. Analysis of immunoblot data revealed significant increases in eNOS levels from 47 ± 22 pixels/μg protein for time controls to 77 ± 36 pixels/μg protein (75% increase) for ischemia in parietal cortex (n = 9 to 10) and 22 ± 10 for control to 40 ± 16 pixels/μg protein (40% increase) for ischemia in hippocampus (n = 7 to 8). Levels of eNOS in cerebellum also tended to be higher but were variable and not significant (n = 5 to 6). In contrast, changes in nNOS levels were not detected at 4 or 6 hours. The increase in eNOS levels detected on immunoblots also was apparent on tissue sections as an increase in intensity of staining. Cyclooxygenase-dependent mechanisms were investigated with respect to the ischemia-induced increase in eNOS levels. Pretreatment with the cyclooxygenase inhibitor indomethacin (5 mg/kg intravenously) abolished the ischemia-induced eNOS increase in parietal cortex and hippocampus (n = 7). Thus, we conclude that the eNOS response is rapid, specific to vessels, and involves an indomethacin-sensitive mechanism.
Keywords: Neonate, eNOS, Cerebral cortex, Hippocampus, Cerebellum, nNOS